2022
DOI: 10.31083/j.rcm2306205
|View full text |Cite
|
Sign up to set email alerts
|

Early Echocardiographic Predictors for Atrial Fibrillation Propensity: The Left Atrium Oracle

Abstract: Atrial fibrillation (AF) results from structural and electrical remodeling of the atria, primarily of the left atrium (LA); therefore, LA changes, both anatomical and functional are recognized as proarrhythmic markers with a powerful prognostic value. Being widely available and noninvasive, echocardiography is used to monitor LA form and function in clinical practice. Early functional (electrical) remodeling of the LA precedes anatomical alterations. Impaired LA functions and reduced atrial compliance due to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 106 publications
(187 reference statements)
0
0
0
Order By: Relevance
“…The mechanism of AF is still controversial and has yet to be fully elucidated. It has been proposed that left atrial (LA) remodeling is strongly associated with the progression of AF, and that LA fibrosis is a major factor leading to LA remodeling [ 5 , 6 ]. Many studies have shown that the LA low-voltage zone (LVZ), which can be identified by high-density electro-anatomic mapping, can be used to evaluate LA fibrosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of AF is still controversial and has yet to be fully elucidated. It has been proposed that left atrial (LA) remodeling is strongly associated with the progression of AF, and that LA fibrosis is a major factor leading to LA remodeling [ 5 , 6 ]. Many studies have shown that the LA low-voltage zone (LVZ), which can be identified by high-density electro-anatomic mapping, can be used to evaluate LA fibrosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%